Proteomic analysis of rice storage proteins in relation to nutrient quality - Md Zin, Noor Hasniza; Tengku Abdul Hamid, Tengku Haziyamin; Ramli, Nur Syazila (2016)
Rice is one of the staple food that is being consumed daily by people around the globe as it provide carbohydrate that will be converted to energy. Besides that, it also provide protein and vitamins to the body. As it has become the main course for the world population, there is a concern rise on the nutritional quality and value of the rice that they consume each day. Apart from that, type of rice that are found commercially at the market also might contribute to different nutritional quality. This nutritional quality is closely related to the seed storage proteins (SSPs) found in rice. Due to this concern, proteomic approach is used to relate the nutritional quality with the different types of commercial rice; white rice, brown rice and glutinous rice in market. The purpose of this study are to investigate the expression level of SSPs of rice from different type of rice, to get the rough idea of different level of SSPs expression of different rice type through one – dimensional electrophoresis (1D), to acquire a better representation of two-dimensional (2D) maps of SSPs spots of different type of rice and to relate the nutrient quality of rice with variability in SSPs expression of different type of rice. The total SSPs of white rice, brown rice and glutinous rice are 6.933± 0.769 mg/ 100 mg, 9.157± 0.396 mg/ 100 mg and 5.388± 0.175 mg/100mg rice grain respectively. From 1D electrophoresis and 2D maps there can be seen that different type of rice were expressed differently. Using MALDI-TOF MS to identify the protein identity, prolamin and glutelin has been found out as the protein that contribute for nutritional quality of rice. In term type of rice with the best nutritional quality, brown rice is the best candidate as it offers high total SSPs which also with the high glutelin.